DFT Calculations, Pro-Apoptotic Effects, and Anti-Infective Investigations of Alkaloids Isolated from the Stem Bark Extract of Enantia chlorantha - Vincent O. Imieje; Ahmed A. Zaki; Mansour A. E. Bashar; Islam Rady; Mohamed A. M. El-Tabakh; Mohamed A. E. Abd El-Aziz; Eman. S. Abou-Amra; Shahd Yasser; Ibraheem M. M. Gobaara; Mohammed A. S. Abourehab; Reham M. Samra; Hussein A. El-Naggar; et al. (MDPI AG, 2024)
Fractionation of the stem bark of Enantia chlorantha Oliv yields three alkaloids, palmatine (1), jatrorrhizine (2), columbamine (3), and β-Sitosterol (4). In this investigation, density functional theory (DFT) calculations were carried out to evaluate the electronic structure and properties of 1-4 by DFT-B3LYP/6-31G level of theory using Gaussian 09 software. The highest occupied molecular orbital (HOMO), lowest unoccupied molecular orbital (LUMO), HOMO-LUMO energy difference (band gap), hardness (η), softness (S), dipole moment (μ), electronegativity (χ), hydrophobicity (logP), topological surface area (TPSA), and energy gap (Eg) were calculated. The in vitro cytotoxicity of the compounds was investigated against MCF-7 and HCT116 cancer cell lines using Wi-38 cells as a control. The compounds inhibited the proliferation of the MCF-7 and HCT116 cell lines and induced apoptosis via upregulation of caspase-3, Bax, PARP cleavage, and downregulation of Bcl-2. DFT analyses revealed that compounds 1 and 3 have smaller energy gaps, 0.072 and 0.071eV, respectively, with the highest dipole moments; hence, these compounds are more chemically reactive and exhibit better modulation of caspase-3 enzyme and inhibitory activities of the MCF-3 and HCT116 cell lines. The antimicrobial and antiparasitic evaluation of 1-4 showed moderate efficacy against the bacterial strains and moderate antiparasitic activity against Cichlidogyrus tilapia.